The shared circulating diagnostic biomarkers and molecular mechanisms of systemic lupus erythematosus and inflammatory bowel disease - Sun, Hao-Wen; Zhang, Xin; Shen, Cong-Cong (Frontiers in Immunology, 2024)
Systemic lupus erythematosus (SLE) is a multi-organ chronic autoimmune disease.Inflammatory bowel disease (IBD) is a common chronic inflammatory disease of the gastrointestinal tract. Previous studies have shown that SLE and IBD share common pathogenic pathways and genetic susceptibility, but the specific pathogenic mechanisms remain unclear. Through various bioinformatics analyses and machine learning algorithms, five hub genes (KLRF1, GZMK, KLRB1, CD40LG, and IL-7R) were ultimately determined as common diagnostic markers for SLE and IBD. ROC curve analysis also showed good diagnostic performance. The outcomes of immune cell infiltration demonstrated that SLE and IBD shared almost identical immune infiltration patterns. Furthermore, the hub gene expression profiles in various immune cells in the SLE population were investigated by using single-cell analysis. This study demonstrates that SLE and IBD share common diagnostic markers and pathogenic pathways such as positive regulation of programmed cell death and inflammatory response. In addition, SLE and IBD show similar immune cell infiltration microenvironments which provides new perspectives for future treatment.